CircBCAR3 accelerates esophageal cancer tumorigenesis and metastasis via sponging miR-27a-3p - Xi, Yong; Shen, Yaxing; Wu, Donglei; Zhang, Jingtao; Lin, Chengbin; Wang, Lijie; Yu, Chaoqun; Yu, Bentong; Shen, Weiyu (Molecular cancer, 2022)
Rationale Circular RNAs (circRNAs) have been demonstrated to contribute to esophageal cancer progression. CircBCAR3 (hsa_circ_0007624) is predicted to be differentially expressed in esophageal cancer by bioinformatics analysis. We investigated the oncogenic roles and biogenesis of circBCAR3 in esophageal carcinogenesis. Methods Functions of circBCAR3 on cancer cell proliferation, migration, invasion, and ferroptosis were explored using the loss-of-function assays. A xenograft mouse model was used to reveal effects of circBCAR3 on xenograft growth and lung metastasis. The upstream and downstream mechanisms of circBCAR3 were investigated by bioinformatics analysis and confirmed by RNA immunoprecipitation and luciferase reporter assays. The dysregulated genes in hypoxia-induced esophageal cancer cells were identified using RNA-seq. Results CircBCAR3 was highly expressed in esophageal cancer tissues and cells and its expression was increased by hypoxia in vitro. Silencing of circBCAR3 repressed the proliferation, migration, invasion, and ferroptosis of esophageal cancer cells in vitro, as well as inhibited the growth and metastasis of esophageal xenograft in mice in vivo. The hypoxia-induced promotive effects on esophageal cancer cell migration and ferroptosis were rescued by circBCAR3 knockdown. Mechanistically, circBCAR3 can interact with miR-27a-3p by the competitive endogenous RNA mechanism to upregulate transportin-1 (TNPO1). Furthermore, our investigation indicated that splicing factor quaking (QKI) is a positive regulator of circBCAR3 via targeting the introns flanking the hsa_circ_0007624-formed exons in BCAR3 pre-mRNA. Hypoxia upregulates E2F7 to transcriptionally activate QKI. Conclusion Our research demonstrated that splicing factor QKI promotes circBCAR3 biogenesis, which accelerates esophageal cancer tumorigenesis via binding with miR-27a-3p to upregulate TNPO1. These data suggested circBCAR3 as a potential target in the treatment of esophageal cancer. Graphical Abstract Hypoxia induces the upregulation of E2F7, which transcriptionally activates QKI in esophageal cancer cells. QKI increases the formation of circBCAR3 by juxtaposing the circularized exons. CircBCAR3 binds with miR-27a-3p to promote TNPO1 expression. CircBCAR3 promoted the proliferation, migration, invasion, and ferroptosis of esophageal cancer cells by miR-27a-3p.